2021
DOI: 10.25217/igcj.v4i1.1199
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Video Game Addiction: The Effects of Composite Regulatory Focus and Interpersonal Competence Among Indonesian Teenagers During COVID-19 Pandemic

Abstract: Video game addiction is recognized as a mental health problem caused by uncontrolled access to video gaming platforms. Proper assistance and counseling programs based on the addiction causing factors are required to reduce the tendencies of video game addiction. The study aims to identify the correlation between regulatory focus theory and interpersonal competence towards the tendencies of video game addiction. The study is a type of cross-sectional research with the adapted psychological scales. A total of 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Moreover, effects like increased aggression or impulsivity have also been observed in this type of addicts (Nugraha et al, 2021).…”
Section: Disadvantages Of Video Gamesmentioning
confidence: 88%
See 1 more Smart Citation
“…Moreover, effects like increased aggression or impulsivity have also been observed in this type of addicts (Nugraha et al, 2021).…”
Section: Disadvantages Of Video Gamesmentioning
confidence: 88%
“…Online gaming platforms and multiplayer features enable people from different parts of the world to connect and interact in a virtual environment. This can lead to the development of friendships, teamwork, and even the formation of communities cantered around shared interests (Nugraha et al, 2021).…”
Section: Advantages Of Video Gamesmentioning
confidence: 99%
“…It has been well-established that video game addiction can cause various deleterious effects on individuals, such as depression, fatigue, loneliness, low self-esteem, and impulsion [ 4 ]. Against this background, examining the risk factors underlying video game addiction has been a focus of relevant studies and interpersonal factors were found to be an important predictor [ 5 ]. At the same time, in spite of the fact that males, who account for the majority of video game users, are always considered to be the main targeted players of game products, female players are increasing and have been gaining an increasingly important role in the game market [ 6 ].…”
Section: Introductionmentioning
confidence: 99%